Agrobiological evaluation of Finnish Solidago virgaurea accessions - Galambosi, Bertalan; Galambosi, Zsuzsanna (MTT, 2008)
The highest biomass potential was measured among the accessions originating from southern parts of Finland. The average fresh and dry herb yields in the second year of cultivation were 4.3 kg and 0.64 kg/m² respectively, which were three times higher, than that of the northern Finnish accessions (1.5 kg/m² and 0.22 kg/m²). For field cultivation the most productive accessions have to be chosen. The results demonstrated that the growth and the yield decreased in the third year of cultivation. This observation has to be confirmed in a longer cultivation period, in order to determine the optimum life cycle of Solidago virgaurea.
Keywords: Pu; medicinal plants; plant genetic resources; Solidago virgaurea